2016
DOI: 10.15578/jra.11.1.2016.85-97
|View full text |Cite
|
Sign up to set email alerts
|

Performa Komoditas Budidaya Laut Pada Sistem Integrated Multi-Trophic Aquaculture (Imta) Di Teluk Gerupuk, Lombok Tengah, Nusa Tenggara Barat

Abstract: <p>Budidaya laut berbasis Integrated Multi-Trophic Aquaculture (IMTA) merupakan opsi pengembangan budidaya perikanan yang sejalan dengan konsep pelestarian lingkungan. Tujuan penelitian ini adalah menganalisis performa komoditas budidaya laut yang pada sistem integrated multi trophic aquaculture (IMTA). Penelitian dilaksanakan di Teluk Gerupuk, Lombok Tengah, Nusa Tenggara Barat, pada bulan Juni-November 2015. Model IMTA yang dikembangkan adalah kombinasi antara ikan kerapu macan (<em>Epinephelus&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…Referring to Saimima et al, (2020), the growth rate of baranong fish with the IMTA system was higher than without IMTA. Research by Radiarta and Erlania (2016) regarding the IMTA system in Grubuk Bay, Lombok, also showed that the specific growth rate of cultured organisms to be 2.17-2.63% per day.…”
Section: Discussionmentioning
confidence: 99%
“…Referring to Saimima et al, (2020), the growth rate of baranong fish with the IMTA system was higher than without IMTA. Research by Radiarta and Erlania (2016) regarding the IMTA system in Grubuk Bay, Lombok, also showed that the specific growth rate of cultured organisms to be 2.17-2.63% per day.…”
Section: Discussionmentioning
confidence: 99%
“…Produksi rumput laut Eucheuma cotonii membutuhkan waktu sekitar 45 hari per siklus [1]. Rumput laut dipanen dengan kadar air mencapai 93% [2], sedangkan kadar air rumput laut kering yang distandarkan oleh SNI maksimum 30% untuk Eucheuma cottonii [3].…”
Section: Pendahuluanunclassified
“…Meanwhile, the oxygen content based on the measurement results (Table 3) shows good conditions for seaweed. The desired dissolved oxygen content in aquaculture systems is about 5 ppm, while the dissolved oxygen concentration of <3 ppm is a barrier for most aquatic organisms (Radiarta & Erlania, 2015).…”
Section: Total Seaweed Carbon Sequestrationmentioning
confidence: 99%